Are you my friend? or not? - Ayers, Beryl; Smith, Craig (Macmillan Education Australia South Yarra, 1998)
Are You My Friend? Or Not? by Beryl Ayers is a charming children's book that explores the themes of friendship, acceptance, and understanding. The story follows a young protagonist who embarks on a quest to find out what true friendship means. As the character interacts with various animals and peers, they learn about the qualities that make a good friend, including kindness, loyalty, and communication. Through playful dialogue and engaging illustrations, the book addresses the complexities of friendships and the importance of being true to oneself and others. Ultimately, it encourages young readers to reflect on their relationships and fosters a sense of empathy and connection.